Educação e hermenêutica : a mediação do cuidado - Brustolin, Fabrício José (2008)
The work consists in a reflection about the content in the work Being and Time from Heidegger, trying to extract deployments to the educational-pedagogic area. The central point is about knowing if it is possible to act oriented by the caution as a possibility of an authentic pedagogy and which implications it brings, specially with the pedagogic relation between teacher and student. This problematic conducts to the reflection on many conceptions which consist in a kind of intrinsic idea in relation to the human existentiality, like caution (Sorge), being there (Dasein), anguish (Angst), chit-chat (Gerede), decay (Verfallen). To keep the discussion alive, the research focuses on the work and avail of secondary commentators specialized on the subject. The work is displayed into two big moments. At first, it tries to extract from the heideggeriana review to the transcended philosophy, an evaluation of the traditional pedagogy, the dichotomy relation between teaching and learning. The work presents, in the second moment, the discussion about the heideggeriano method, having it as a reference to thin k about a pedagogic research that can break with the near empiric, allowing the own researcher discuss about the ingenuous initial formulation of its investigation